2019
DOI: 10.1111/oik.06054
|View full text |Cite
|
Sign up to set email alerts
|

Examining the link between competition and negative co‐occurrence patterns

Abstract: Negative species co‐occurrence patterns have long intrigued ecologists because of their potential link to competition. Although manipulative field experiments have consistently revealed evidence of competition in natural communities, there is little evidence that this competition produces negative co‐occurrence patterns. Evidence does suggest that abiotic variation, dispersal limitation and herbivory can contribute to patterns of negative co‐occurrence among species; it is possible these influences have obscur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 53 publications
3
25
0
Order By: Relevance
“…Although they are often time consuming and costly, they can increase our knowledge on interactions while remaining in the world of co‐occurrences. As an example, Brazeau & Schamp (2019) have recently studied experimentally the link between competition and negative co‐occurrence for flowering plants. Similarly, Kopelke et al (2017) gathered a large data set directly recording the interaction between willow tree species and sawflies, a group of parasites feeding on willow leaves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although they are often time consuming and costly, they can increase our knowledge on interactions while remaining in the world of co‐occurrences. As an example, Brazeau & Schamp (2019) have recently studied experimentally the link between competition and negative co‐occurrence for flowering plants. Similarly, Kopelke et al (2017) gathered a large data set directly recording the interaction between willow tree species and sawflies, a group of parasites feeding on willow leaves.…”
Section: Discussionmentioning
confidence: 99%
“…While some recent studies have unveiled such a regular signal (e.g. Gotelli et al, 2010; Cardillo, 2011), other have shown that the signal is blurred and diluted in complex networks (Cazelles et al, 2016) or even absent (Brazeau & Schamp, 2019) and thus, the existence of a signal and properties thereof are still debated.…”
Section: A Rich and Long Debatementioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the correlative nature of network interaction, the complexity and non-linear dynamics of communities inferring interactions from covariance should be viewed with skepticism until coupling with empirical data to prove interactions (i.e. colocalization, stable isotope labeling, and co-culturing assays) 84 , 85 . This is illustrated by recent papers incorporating known metabolite transport, usage, and production with species co-occurrence into a network and finding both known and yet-to-be-confirmed interactions ( Figure 2C ) 80 , 81 .…”
Section: The Continuing Rise Of Omicsmentioning
confidence: 99%
“…2) co-occurrence patterns similar to those we observed. However, we appreciate that such patterns 430 may also be generated by other ecological processes (Brazeau & Schamp, 2019). Thus, in order 431 to strengthen inferences for particular assembly processes which could be at play, we explicitly 432 scrutinized species' co-occurrence relationships in light of their ecological differences (i.e., 433 traits) within the context of classical and contemporary theories on interspecific competition 434 ( Fig.…”
mentioning
confidence: 99%